Comparative efficacy and safety of radiotherapy/cetuximab versus radiotherapy/chemotherapy for locally advanced head and neck squamous cell carcinoma patients: a systematic review of published, primarily non-randomized, data. (December 2020) - Mei, Mei; Chen, Yu-Huan; Meng, Tian; Qu, Ling-Han; Zhang, Zhi-Yong; Zhang, Xiao
Background: Cetuximab (CTX) has been approved to be administered concurrently with radiotherapy (RT) to treat locally advanced head and neck squamous cell carcinoma (HNSCC). The aim of this study was to assess the efficacy and safety of concurrent CTX with RT (ExRT). Method: The PubMed, Cochrane Library, EMBASE databases were systematically searched to find relevant articles. The combined hazard ratio (HR), risk ratio (RR) and 95% confidence interval were calculated to assess the efficacy and safety of ExRT in contrast to concurrent platinum-based chemotherapy with RT (ChRT). Results: In total, 32 articles with 4556 patients were included. The pooled HRs indicated that ExRT achieved an unfavorable overall survival (HR: 1.86, p < 0.0001), disease-specific survival (HR: 2.58, p = 0.002), locoregional control (HR: 1.94, p < 0.00001), and progression-free survival (HR: 2.04, p = 0.003) compared with ChRT for locally advanced HNSCC patients. In human papillomavirus-positive patient subgroups, ExRT showed inferior disease-specific survival (HR: 2.55, p = 0.009) and locoregional control (HR: 2.27, p < 0.0001) in contrast to ChRT. Additionally, ExRT increased the occurrence of mucositis (RR: 1.17, p < 0.005), skin toxicity (RR: 6.26, p < 0.00001), and infection (RR: 2.27, p = 0.04) compared with non-CTX groups (ChRT and RT), and was associated with lower incidence of anemia (RR: 0.35, p = 0.009), leukocytopenia (RR: 0.17, p < 0.0001), neutropenia (RR: 0.06, p < 0.0001), nausea/vomiting (RR: 0.23, p < 0.0001), and renal toxicity (RR: 0.14, p = 0.007). Conclusion: ChRT should remain the standard treatment for locally advanced HNSCC patients. ExRT was recognized as an effective alternative treatment for locally advanced HNSCC patients who experienced unbearable toxicities caused by non-CTX treatments.